Comparative analysis of the level of aggression between the women practicing judo and Brazilian jiu-jitsu - Janowska, Patrycja; Wojdat, Marta; Bugajska, Emilia; Paradowska, Magdalena; Wolska, Beata; Adam, Marek; Stępniak, Robert (Journal of Education, Health and Sport, 2018)
Aim: Comparison of the level of aggression between the women practicing judo and Brazilian jiu-jitsu against the average aggression level among Polish women. Materials and methods: A group of 30 women practicing judo and a group of 27 women practicing jiu-jitsu were tested by using a questionnaire to show the aggression level- ‘Aggression questionnaire’ by Buss, Amity Institute with Polish adaptations. Results: The total decreasing in the aggression level was observed among the group of women practicing judo and partial among women practicing Brazilian jiu-jitsu. Conclusion: A longstanding practice of Brazilian jiu-jitsu by women results in decreasing of aggression level, what can be later used during planning therapeutic schemes.